Successful Outcome of Programmed Death 1 Blockade Plus GemOx for Epstein-Barr Virus-Associated Primary Nodal T/NK Cell Lymphoma: A Case Report - Xia, Liang; Zhang, Han-Shuo; Bao, Jing; Zhao, Yu-Chen; Xia, Hai-Long (Frontiers in Oncology, 2021)
Epstein-Barr virus (EBV)-associated lymph nodal T/NK cell lymphoma (nodal TNKL) is a rare and aggressive malignancy with an extremely poor prognosis. Although treatments of extranodal NK/T cell lymphoma are frequently reported, the characteristics and pathogenesis of EBV-associated nodal TNKL are different. However, there is no known effective therapy regimen at present. Here, we reported the clinical efficacy and feasibility of the programmed death 1 (PD-1) blockade therapy regimen in an elderly female patient with EBV-associated nodal TNKL. The patient failed to respond to cyclophosphamide, doxorubicin, vindesine, and prednisone regimen but achieved complete response after three cycles of anti-PD-1 antibody (tislelizumab) combined with gemcitabine and oxaliplatin (GemOx) regimen. The finding indicated that tislelizumab combined with the GemOx regimen may be a potent salvage regimen for EBV-associated nodal TNKL.